Cognitive mapping concept of resource management for the viability of local communities - K. Trostianska; I. Semencha; M. Yerina (Global Journal of Environmental Science and Management)
The local community is a complex socio-economic system, and its ability to function for an indefinitely long period of time (viability) is not investigated sufficiently today. The purpose of the research was, using the cognitive mapping, propose to the local community management developing their own management strategies to ensure its viability. Considering the weakly structured subject area of resource management for the viability of the local community and the complex dynamic nature of socio-economic processes, fuzzy cognitive reflection was suggested as a tool that provides opportunities for modeling the inherent complexity and uncertainty associated with socio-economic systems. This research shows a system of relations between concepts in the form of a causative network – a cognitive map of the resource management of a local community and proposes scales for measuring the concepts. During the simulation experiments, managed, indirectly managed and unmanaged resources for the viability of a local community were defined. In modeling, own income per inhabitant has been chosen as the target concept and as an indicator of the potential of an independent choice of direction for the development of the local community with the view toward the construction of resource management scenarios for the local community's viability. As a result of the simulation, there were proposed some strategies for the growth of ‘own income per inhabitant’ and some recommendations were given for building management scenarios within these strategies.